Organizational Specifics of the Volunteer Movement: Comparing the Experience of Russia and France - Marina Spirina (Journal of Economic Sociology, 2015)
The article presents a comparative analysis of the internal structure and principles of the organization of volunteer associations in Russia and France from the perspective of the sociology of organizations. The theoretical framework of the study combines the concepts of the neo-institutionalist approach in economic sociology and the network approach to organizations. Data are drawn from a series of in-depth expert interviews with the leaders of socially-oriented volunteer organizations in France and Russia (14 interviews). The author also conducted analysis of legal documents and communication materials of volunteer associations in each of the countries studied (approximately 40 documents totaling over 200 pages of text).It appears that the Russian and French volunteer sectors differ not only in structure and legal status of voluntary organizations, but also in the conceptual definition of volunteering. Drawing on empirical data, it was found that the French volunteer associations exist in a structured institutional environment, while Russian voluntary associations perform in a poorly structured, constantly changing environment, the main problem of which is the lack of cognitive and socio-political legitimacy. Thus, the French model of volunteering is more similar to the mechanism of institutional organizations, while Russian voluntary associations are more typical of networked organizations.This research suggests a different vision of the nature of voluntary organizations and argues that it is impossible to ignore national characteristics in the development of social policy. Conclusions drawn from this research could be applied to the development of public policy regarding the non-profit sector in Russia.